A PROCESS MODEL OF CULTURAL INFLUENCES ON CORPORATE ENTREPRENEURSHIP - SEKHUKHUNE, BOITUMELO (My University, 2011)
Making innovation happen is one of the most important issues currently facing most companies in understanding how best to unlock value. As important as it is, it remains a fairly elusive value for most organisations, which, while acknowledging its importance, lack the ability to leverage it for value creation, much the same way organisational culture is acknowledged to be an important factor in the success of organisations. Yet, despite all its proclaimed values, 70% of all corporate culture change efforts result in failure. The topic and practice of corporate entrepreneurship have attracted considerable interest from both corporate practitioners and academics alike. Much of the interest in this area is based on the acknowledgement that innovation is assumed to have critical importance for firms competing in rapidly evolving industries. Within this interest, a particularly promising area of research focus has been that of entrepreneurial cognition. However, the focus in the area has largely been on individual entrepreneurship, the way entrepreneurs think, the individual decision-making processes and heuristics adopted by entrepreneurs. In line with this focus, there is an increased awareness of the need for a greater understanding of the processes and strategies of corporate entrepreneurship, particularly in the manner in which culture affects these entrepreneurial cognitive processes. The purpose of this research is to develop a model that provides a description of the process of how culture affects corporate entrepreneurship. The rationale of the research is to help fill a gap in the literature by providing a model that describes corporate entrepreneurship as a process that is also affected by corporate culture.
MBA thesis - WBS
Keywords: Corporate entrepreneurship; Culture, Influence of